Determination of Calcium Level (Ca) and Iron (Fe) on Red and Green Spinaches at Parigi Moutong - Vina Febriyani; Nurdin Rahman; Ratman Ratman (Jurnal Akademika Kimia, 2019)
This research aims to determine calcium level (Ca) and iron (Fe) on red and green spinaches at Parigi Moutong. The method used in this research is spectrodirect method. The research result shows that the calcium level (Ca) and iron (Fe) on green spinach was 0.97 mg/kg and red spinach was 58.33 mg/kg at Pelawa village, while the calcium level (Ca) and iron (Fe) on green spinach was 0.62 mg/kg and red spinach was 50.39 mg/kg. From the research results obtained, it can be seen that the level of calcium and iron on red and green spinach in where the red spinach levels higher than the green spinach levels.